Effect of training status and sex on force asymmetry in national level volleyballers - McGown, R.; Mara, J.; Tatham, J. (Journal of Australian Strength and Conditioning, 2018)
Peak force bilateral asymmetry may be highly individualised rather than dependent on training status and sex in national level volleyballers.